Menangkal Radikalisme Melalui Pengajian Budaya di Padepokan Cakra Manggilingan Kabupaten Nganjuk - Bustanul Arifin (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
This research is related to the interest in activities at Padepokan Cakra Manggilingan Tanjunganom Nganjuk which instill monotheism and love for the homeland through cultural studies, with a qualitative descriptive approach, the results of this study are that cultural studies are one of the effective media to prevent the spread of radical ideology. The participants carefully practiced the teachings of Islam, drew closer, and felt inferior before Allah subhanahu wataala and loved the homeland and avoided acts of violence in religion.